Partisipasi Masyarakat dalam Pengelolaan Sumber Daya Air Berkelanjutan di Karo - Syafrizal Alfala; Cut Nuraini (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Sustainable water resource management is a crucial issue, especially in horticultural agricultural areas such as Berastagi, Karo Regency, North Sumatra. This area is known for its abundant water resources, but the challenge in optimizing water distribution and quality is still a problem. This study aims to analyze the level of community participation in water resource management in Berastagi and to develop a sustainable management strategy using the SWOT approach. The method used in this study is a SWOT analysis that considers strengths, weaknesses, opportunities, and threats in water management. The results show that community participation in technical aspects is quite high, but still low in terms of planning and evaluation. The main strength factors are abundant water resources and support from the farming community, while weaknesses lie in limited infrastructure and water pollution from agricultural activities. The main opportunities for sustainable water management include irrigation modernization and increased government regulation, while the main threats are the impacts of climate change and the use of chemicals in agriculture that have the potential to pollute water. From this SWOT analysis, it is recommended to develop technology-based irrigation infrastructure, increase socialization and community education to increase involvement in water management, and collaboration between the government, community, and research institutions. It is expected that this strategy can strengthen sustainable and adaptive water resource management in the Berastagi horticultural area.